Tendon vibration changes perceived joint angle independent of voluntary body motion direction in virtual environments. (4th March 2021) - Hagimori, Daiki; Isoyama, Naoya; Yoshimoto, Shunsuke; Sakata, Nobuchika; Kiyokawa, Kiyoshi
ABSTRACT: The consistency between the virtual environment and the real environment perceived by the body is important, and sensory stimulation technologies that can enhance the sense of self-ownership and self-agency for the virtual body are required. The objective of this study is to clarify the effect of tendon vibration stimulation on the perception on the body when the inconsistency of the body motion is generated by virtual reality (VR) experience in which the virtual body motion is equal to or more than the real body motion. We carried out experiments to clarify perceptual characteristics such as the relationship between the intensity of the tendon vibration stimulus and the degree of perceptual angle modulation. When the vibration stimulus provides clarity of illusion, the change was about 17 degrees in flexion and about −12 degrees in extension in the same-direction group. It is suggested that the perceived angle can be changed in any direction by the tendon vibration stimulation, regardless of the actual motion direction. The experimental results suggest that the perceptual modulation by tendon vibration stimulation may be one of the solutions to the inconsistency between virtual and real bodies. GRAPHICAL ABSTRACT: UF0001